Comparison of the state of Polish-Lithuanian relations before and after Russia’s aggression against Ukraine in 2014 - Bartoszewski, Bartosz (Boundaries and Spheres of Influence in Domestic Politics and International Relations, 2023)
The aim of the following work is to show how the Russian aggression against Ukraine in 2014 influenced the change in Polish-Lithuanian relations. The first part of the article is a historical outline of Polish-Lithuanian relations, with particular emphasis on the specificity of the formation of Lithuanian national identity in the 19th century. Then, the main problems faced by the Polish minority in Lithuania since the country gained independence in 1991 were indicated. These issues are part of the overall picture of Polish-Lithuanian relations, which have been gradually improving since 2014. The last element of the work are selected examples that show a change in the perception of the Polish minority by the authorities in Vilnius. Joint Polish-Lithuanian security initiatives have also been indicated, which gained new meaning after the new Russian aggression against Ukraine in 2022.